HERMIONE, EVOLUTION OF ATe-BEARING EPITHERMAL MINERALIZATION, ARGOLIS, HELLAS - Tombros, S.; St. Seymour, K. (Bulletin of the Geological Society of Greece, 2007)
The Cu-Te-bearing pyrite deposits of Hermione, Argolis are hosted in Miocenic ophiolites. The ophiolites are overlain by a shale-sandstone formation with intercalations of limestones and manganiferous sedimentary rocks. The ore deposits form irregular lenticular or stratiform ore bodies, and veins. These ore bodies are related to volcanic activity in an arc-related rift at the margins of a palaeocontinent. Late N- to NNE-trending, sinistral, milky quartz-pyrite-calcite veins cut the host ophiolites. Alteration haloes of quartz-calcite, albite-sericitechlorite, and chalcedony-epidote-clay minerals are developed in the lavas as concentric shells, or as envelops that parallel the quartz veins. The telluriumbearing mineralization is developed in two successive stages, characterized by the assemblages: pyrite-(pyrrhotite)-magnetite-chalcopyrite-sphalerite (Stage I) and galena-sphalerite-freibergite-marcasite-chalcocite (Stage II), followed by a supergene stage. The cobaltiferous pyrite-chalcopyrite geothermometer defined two ranges of last-equilibration temperatures: 220° to 250°Cfor Stage I, and 120° to 195°Cfor Stage II. The calculated δ18 Ο and SD compositions of the mineralizing fluids, at 200° and 250°C, reflect the dominance of a magmatic component. The calculated δ SH2S fluid values reveal a magmatic source for the sulphur, with minor contribution from submarine sediments, whereas tellurium is proposed to be derived from a mafic-ultramafic source.